<u>Answer:</u>
Swati - 465 , Matt - 289
<u>Explanation:</u>
Let Swati's score be x and Matt's score be y.
Since Swati won the game her score is obviously higher.
We are given the sum and difference between their scores which we can write as , x + y = 754 and x - y = 176.
Solving these two equations by adding them we get 2x = 930 so x = 465. Substituting x in x - y = 176 we get y = 289
Thus Swati scored 465 points and Matt scored 289 points.
Answer:
<em>The correct answer is: A</em>
Step-by-step explanation:
<u>Points on a Numeric Line</u>
The numeric line shown in the figure has four points A, B, C, and D. It's clear that each marked division of the line has a value of 1/4 units and all four points are below the reference zero, thus all are negative.
Point A is clearly on the -2 mark, thus
A=-2
Point B is one mark above A, thus it's located at:
![B=-2+\frac{1}{4}=-\frac{7}{4}=-1\frac{3}{4}](https://tex.z-dn.net/?f=B%3D-2%2B%5Cfrac%7B1%7D%7B4%7D%3D-%5Cfrac%7B7%7D%7B4%7D%3D-1%5Cfrac%7B3%7D%7B4%7D)
![B=-1\frac{3}{4}](https://tex.z-dn.net/?f=B%3D-1%5Cfrac%7B3%7D%7B4%7D)
Point C is one mark below -1, thus:
![C=-1-\frac{1}{4}=-1\frac{1}{4}](https://tex.z-dn.net/?f=C%3D-1-%5Cfrac%7B1%7D%7B4%7D%3D-1%5Cfrac%7B1%7D%7B4%7D)
Finally, point D is one mark below 0:
![D=-\frac{1}{4}](https://tex.z-dn.net/?f=D%3D-%5Cfrac%7B1%7D%7B4%7D)
The correct answer is: A
Answer:
The answer to this equation will be 2 for x
Step-by-step explanation:
Hope this Helped
Answer:
B. ![\frac{-4x + 7}{2(x - 2)}](https://tex.z-dn.net/?f=%20%5Cfrac%7B-4x%20%2B%207%7D%7B2%28x%20-%202%29%7D%20)
Step-by-step explanation:
Simplify the given expression to determine its equivalent expression in the given options.
![\frac{\frac{3}{x - 1} - 4}{2 - \frac{2}{x - 1}}](https://tex.z-dn.net/?f=%20%5Cfrac%7B%5Cfrac%7B3%7D%7Bx%20-%201%7D%20-%204%7D%7B2%20-%20%5Cfrac%7B2%7D%7Bx%20-%201%7D%7D%20)
![\frac{\frac{3}{x - 1} - \frac{4}{1}}{\frac{2}{1} - \frac{2}{x - 1}}](https://tex.z-dn.net/?f=%20%5Cfrac%7B%5Cfrac%7B3%7D%7Bx%20-%201%7D%20-%20%5Cfrac%7B4%7D%7B1%7D%7D%7B%5Cfrac%7B2%7D%7B1%7D%20-%20%5Cfrac%7B2%7D%7Bx%20-%201%7D%7D%20)
![\frac{\frac{3 - 4(x - 1)}{x - 1}}{\frac{2(x - 1) - 2}{x - 1}}](https://tex.z-dn.net/?f=%20%5Cfrac%7B%5Cfrac%7B3%20-%204%28x%20-%201%29%7D%7Bx%20-%201%7D%7D%7B%5Cfrac%7B2%28x%20-%201%29%20-%202%7D%7Bx%20-%201%7D%7D%20)
![\frac{\frac{3 - 4x + 4}{x - 1}}{\frac{2x - 2 - 2}{x - 1}}](https://tex.z-dn.net/?f=%20%5Cfrac%7B%5Cfrac%7B3%20-%204x%20%2B%204%7D%7Bx%20-%201%7D%7D%7B%5Cfrac%7B2x%20-%202%20-%202%7D%7Bx%20-%201%7D%7D%20)
![\frac{\frac{-4x + 7}{x - 1}}{\frac{2x - 4}{x - 1}}](https://tex.z-dn.net/?f=%20%5Cfrac%7B%5Cfrac%7B-4x%20%2B%207%7D%7Bx%20-%201%7D%7D%7B%5Cfrac%7B2x%20-%204%7D%7Bx%20-%201%7D%7D%20)
![\frac{-4x + 7}{x - 1} * \frac{x - 1}{2x - 4}](https://tex.z-dn.net/?f=%20%5Cfrac%7B-4x%20%2B%207%7D%7Bx%20-%201%7D%20%2A%20%5Cfrac%7Bx%20-%201%7D%7B2x%20-%204%7D%20)
(x - 1) cancels (x - 1)
![\frac{-4x + 7}{1} * \frac{1}{2x - 4}](https://tex.z-dn.net/?f=%20%5Cfrac%7B-4x%20%2B%207%7D%7B1%7D%20%2A%20%5Cfrac%7B1%7D%7B2x%20-%204%7D%20)
![\frac{(-4x + 7)1}{1(2x - 4)}](https://tex.z-dn.net/?f=%20%5Cfrac%7B%28-4x%20%2B%207%291%7D%7B1%282x%20-%204%29%7D%20)
![\frac{-4x + 7}{2x - 4}](https://tex.z-dn.net/?f=%20%5Cfrac%7B-4x%20%2B%207%7D%7B2x%20-%204%7D%20)
![\frac{-4x + 7}{2(x - 2)}](https://tex.z-dn.net/?f=%20%5Cfrac%7B-4x%20%2B%207%7D%7B2%28x%20-%202%29%7D%20)
Answer:
B is the correct answer.
Step-by-step explanation:
graph attached below, with red as the parent function (f(x)=3^x) and blue as the change (f(x)=3^x-8).